2012
DOI: 10.1029/2011jf002057
|View full text |Cite
|
Sign up to set email alerts
|

Using hilltop curvature to derive the spatial distribution of erosion rates

Abstract: [1] Erosion rates dictate the morphology of landscapes, and therefore quantifying them is a critical part of many geomorphic studies. Methods to directly measure erosion rates are expensive and time consuming, whereas topographic analysis facilitates prediction of erosion rates rapidly and over large spatial extents. If hillslope sediment flux is nonlinearly dependent on slope then the curvature of hilltops will be linearly proportional to erosion rates. In this contribution we develop new techniques to extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
381
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 168 publications
(424 citation statements)
references
References 132 publications
26
381
0
2
Order By: Relevance
“…Predicted slope stability, modeled in part as a function of TWI, was assessed by Tarolli and Tarboton (2006), who demonstrated that, for large-scale landsliding, a lidar-derived DEM downsampled to 10 m resolution was more suitable to identify landslide hazard than the highest-resolution data available. This highlights the requirement to consider the scale of the process being studied when selecting the appropriate grid resolution for a study and corresponds to the challenges of selecting the correct size of smoothing window to capture processes on a suitable scale (e.g., Roering et al, 2010, Hurst et al, 2012, and Grieve et al, 2016b.…”
Section: Previous Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Predicted slope stability, modeled in part as a function of TWI, was assessed by Tarolli and Tarboton (2006), who demonstrated that, for large-scale landsliding, a lidar-derived DEM downsampled to 10 m resolution was more suitable to identify landslide hazard than the highest-resolution data available. This highlights the requirement to consider the scale of the process being studied when selecting the appropriate grid resolution for a study and corresponds to the challenges of selecting the correct size of smoothing window to capture processes on a suitable scale (e.g., Roering et al, 2010, Hurst et al, 2012, and Grieve et al, 2016b.…”
Section: Previous Workmentioning
confidence: 99%
“…However, all such work was performed on high-resolution topography and the impact of grid resolution on these metrics is unknown. Roering et al (2007) and Hurst et al (2012) demonstrated that the curvature of ridgelines measured from high-resolution topography can be used as a proxy for erosion rates in soil-mantled landscapes. This observation has been used in many studies in which cosmogenic radionuclide-derived erosion rates are unavailable (Pelletier et al, 2011;Hurst et al, 2013c, b;Grieve et al, 2016b).…”
Section: Introductionmentioning
confidence: 99%
“…1 and includes the possibility of filtering (step 1) and degrading (step 2) the DEM; the effects of both treatments are examined in the discussion. A slope raster is then generated by fitting a polynomial surface to topographic data and taking the derivative of this surface (Hurst et al, 2012;Grieve et al, 2016) (step 3). Steps 4 and 5 are novel algorithms developed in this study to isolate scarps and platforms.…”
Section: Methodsmentioning
confidence: 99%
“…Topographic input data are therefore clipped to the landward limit of the platform, at the discretion of the user. In the preparation stage, local slope is calculated from the DEM by fitting a second-order polynomial surface (Hurst et al, 2012) with a window radius of 3 times the horizontal resolution of the DEM, selected because it is the minimum radius needed to calculate slope with this method. The DEM may be passed through a Wiener filter (Wiener, 1949;Robinson and Treitel, 1967) to reduce noise from lidar datasets and/or degraded by averaged subsampling before the determination of slope to match complementary datasets.…”
Section: Preprocessing Topographic Datamentioning
confidence: 99%
“…In the preparation stage, local slope is calculated from the DEM by fitting a second order polynomial surface (Hurst et al, 2012) with a circular window radius equal to three times the horizontal resolution of the DEM. The DEM may be passed through a Wiener filter (Wiener, 1949;Robinson and Treitel, 1967) to reduce noise from lidar datasets and/or degraded by averaged subsampling 20 before the determination of slope to match complementary datasets.…”
Section: Preprocessing Topographic Datamentioning
confidence: 99%